SME LOAN DECISION-MAKING PROCESS: THE DECLINING ROLE OF HUMAN CAPITAL - Ottavia; Enkhbold Chuluunbaatar; Shiann-Far Kung; Ding-Bang Luh (Asian Academy of Management Journal, 2011)
This study is intended to establish relationships among a borrower's attributes, the likelihood of loan approval, and the effect of lender's human capital in the SME loan-granting process. A conjoint analysis has been used as the main analytical tool. The results showed that: (1) a borrower's attributes are all positively related to the likelihood of loan approval on different levels, (2) officers place different weights on a borrower's attributes, and (3) human capital factors do not have significant roles in the SME loan-granting process.